(NDRG2) stimulates amiloride-sensitive Na+ currents in Xenopus laevis oocytes and fisher rat thyroid cells - Rauh, Robert; Korbmacher, Christoph; et al. (Journal of Biological Chemistry, 2007)
Regulation of the epithelial sodium channel (ENaC) is highly complex and may involve several aldosterone-induced regulatory proteins. The N-Myc downstream-regulated gene 2 (NDRG2) has been identified as an early aldosterone-induced gene. Therefore, we hypothesized that NDRG2 may affect ENaC function. To test this hypothesis we measured the amiloride-sensitive (2 μM) whole cell current (ΔIami) in Xenopus laevis oocytes expressing ENaC alone or co-expressing ENaC and NDRG2. Co-expression of NDRG2 significantly increased ΔIami in some, but not, all batches of oocytes tested. An inhibitory effect of NDRG2 was never observed. Using a chemiluminescence assay we demonstrated that the NDRG2-induced increase in ENaC currents was accompanied by a similar increase in channel surface expression. The stimulatory effect of NDRG2 was preserved in oocytes maintained in a low sodium bath solution to prevent sodium feedback inhibition. These findings suggest that the stimulatory effect of NDRG2 is independent of sodium feedback regulation. Furthermore, the stimulatory effect of NDRG2 on ENaC was at least in part additive to that of Sgk1. A short isoform of NDRG2 also stimulated ΔIami. Overexpression of NDRG2 and ENaC in Fisher rat thyroid cells confirmed the stimulatory effect of NDRG2 on ENaC-mediated short-circuit current (ISC-ami). In addition, small interference RNA against NDRG2 largely reduced ISC-ami in Fisher rat thyroid cells. Our results indicate that NDRG2 is a likely candidate to contribute to aldosterone-mediated ENaC regulation. © 2007 by The American Society for Biochemistry and Molecular Biology, Inc.
UnivIS-Import:2015-03-09:Pub.2007.med.IPK.LPVP.ndrg2s